Uncovering Molluscs Diversity in Mandalika Coastal Through eDNA Metabarcoding - Candri, Dining Aidil; Mursal Ghazali; Tri Wahyu Setyaningrum; Mardiati, Aina Ul; Muhammad Syach Maulad Ichfa (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research The environmental DNA (eDNA) method successfully identified four species of molluscs (Monetaria , M. annulus, M. obvelata, and Phyllaplysia sp.) and two family taxa (Strombidae and Cypraeidae) from the seagrass and coral reef ecosystems on the Mandalika coast. The species annulus, M. obvelata, and Phyllaplysia sp were detected in the coastal area of ​​Mandalika for the first time using the eDNA approach, although they had never been recorded observationally in this area before. The eDNA method is able to detect species that are difficult to observe directly, such as Phyllaplysia, which have never been reported in the coral reef ecosystem of Mandalika. This study emphasizes the urgency of sustainable coastal area management with an eDNA-based scientific approach to monitor diversity, detect rare species, and evaluate the impact of human activities on the ecosystem. Abstract Molluscs are one of the main taxa in coastal ecosystems that play an important role in the food chain, bioindicators, and have high economic value. However, the limitations of conventional methods in detecting species that live hidden in complex ecosystems, such as seagrass and coral reefs, are a challenge in biodiversity monitoring. This study aimed to explore the diversity of mollusc species in the Mandalika coastal area using an eDNA metabarcoding approach. This study used the environmental DNA (eDNA) metabarcoding method to identify the diversity of molluscs in the coastal ecosystem of Mandalika, Central Lombok. The sites including Kuta Beach, Gerupuk Bay, and Aan Cape along the Mandalika coastal that contain both seagrass bed and coral reef ecosystems. Two samples were taken from each site in both the seagrass bed and coral reef ecosystems. Analysis of six water samples resulted in 99 ASVs and 116,611 final sequences, with 10 ASVs (50,960 sequences) identified as Mollusca taxa, all from the Gastropoda class. Four species were successfully identified, including Monetaria sp. M. obvelata, M. annulus and Phyllaplysia sp. that had not previously been reported through direct observation or conventional identification methods in Mandalika coastal area. Species diversity varied between locations and was influenced by environmental factors such as temperature, pH, salinity, phosphate, and anthropogenic pressure. These results show that eDNA metabarcoding is an effective tool in detecting mollusc species, even in hard-to-reach habitats, and support the urgency of scientific data-based mollusc conservation management.